Violation and Satisfaction. A Sociology of Law Study of Non-Pecuniary Damages to Victims of Crime. Replication. - Dahlstrand, Karl (Lund University, 2022)
This study is a replication of an original study that was published about 10 years ago in 2012 in the doctoral dissertation "Violation and Satisfaction: A Sociology of Law Study of Non-Pecuniary Damages to Victims of Crime" by Karl Dahlstrand. The replication study was conducted to investigate similarities and changes in the "general legal consciousness" in relation to compensation for violations of crime victims and has been carried out in collaboration with the Swedish Crime Victim Authority, funded by “Ulla V Bondeson's Foundation for socio-legal and criminological research" and with Peter Bergwall as research assistant.

The project collected data through two surveys: one web survey with repondents from the general public, and one postal survey mailed to crime victims who received criminal injury compensation from the Swedish Crime Victim Authority.

For more information on the original study, refer to the catalogue entry for "Violation and Satisfaction. A Sociology of Law Study of Non-Pecuniary Damages to Victims of Crime": https://doi.org/10.5878/002817

For more information on the replication study and its methods, refer to the (Swedish only) report: "Kränkning och upprättelse. En replikation av en rättssociologisk enkätstudie" https://lup.lub.lu.se/record/40517edf-4477-4192-ba91-a872f20a9da0

2021 Allmänheten reversed.sav: SPSS file with survey responses from the online survey targeting the general public.
2021 Brottsoffer reversed.sav: SPSS file with survey responses from individuals who have received criminal injury compensation from the Swedish Crime Victim Authority.
The data is also available in .csv format (UTF-8).

Refer to the attached surveys (Swedish) as well as the published report for the survey structure. Refer to the attached code books for variable descriptions.
The survey text answers (single comment field) are not included in this dataset.

Studien är en replikation på en ursprunglig studie som publicerades 2012 i avhandlingen "Kränkning och upprättelse. En rättssociologisk studie av kränkningsersättning till brottsoffer" av Karl Dahlstrand. Replikationen gjordes för att undersöka likheter och förändringar i det "allmänna rättsmedvetandet" i relation till kränkningsersättning till brottsoffer och har genomförts i samarbete med Brottsoffermyndigheten, finansierats av ”Ulla V Bondesons Stiftelse för rättssociologisk och kriminologisk forskning” och med Peter Bergwall som forskningsassistent.

Projektet består av empiriinsamling i form av två enkätundersökningar; en webbenkät som vänder sig till urval av allmänheten och en traditionell postenkät som vänder sig till ett urval brottsoffer som erhållit kränkningsersättning från Brottsoffermyndigheten.

För mer information om den ursprungliga studien, se katalogpost för ”Kränkning och upprättelse. En rättssociologisk studie av kränkningsersättning till brottsoffer”: https://doi.org/10.5878/002817

För mer information om replikationsstudien och dess metod, se rapporten "Kränkning och upprättelse. En replikation av en rättssociologisk enkätstudie" https://lup.lub.lu.se/record/40517edf-4477-4192-ba91-a872f20a9da0

2021 Allmänheten reversed.sav: SPSS-fil med besvarade webbenkäter av respondentgruppen "allmänheten".
2021 Brottsoffer reversed.sav: SPSS-fil med besvarade enkäter av respondentgruppen "brottsoffer som fått kompensation".
Datafiler i .csv-format (UTF-8) finns också tillgängliga.

Se medföljande enkäter samt den publicerade rapporten för struktur. Se medföljande kodböcker för variabelbeskrivningar.
Enkäternas fritextfält för kommentarer finns inte publicerat i detta dataset.
Kränkning och upprättelse. En rättssociologisk studie av kränkningsersättning till brottsoffer. Replika.
Keywords: law enforcement; upprätthållande av lag och ordning; crime victims; brottsoffer; legal damages; skadestånd; restorative justice; reparativ rättvisa; sociology of law; rättssociologi; violation; kränkning; LAW, CRIME AND LEGAL SYSTEMS; LAG, BROTTSLIGHET OCH RÄTTSSYSTEM; Other Legal Research; Annan rättsvetenskaplig forskning